Perkembangan Pemikiran Islam Modern: Studi Kritis Terhadap Gerakan Ahmadiyah - Mustin, Hilgha; Abbas, Nurlelah; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Ahmadiyyah movement is one of the significant manifestations of modern Islamic thought that emerged in response to the spiritual, intellectual, and political crisis among Muslims in late 19th-century India. Founded by Mirza Ghulam Ahmad, the movement introduced controversial theological claims such as prophethood, new revelation, and the belief that he was the Promised Messiah and Mahdi. These doctrines were met with strong opposition from mainstream Muslim communities who uphold the belief in the finality of prophethood with Muhammad SAW. This article aims to explore the history, core doctrines, and the development of Ahmadiyyah in Indonesia using a qualitative, literature-based approach. The findings indicate that despite theological and social rejection, Ahmadiyyah continues to survive and contribute to the discourse on Islamic reform, especially in areas such as rationality, pluralism, and religious literacy. In Indonesia, Ahmadiyyah was initially received by some modernist Muslim groups but was later widely rejected following a fatwa issued by the Indonesian Ulema Council (MUI) declaring it deviant. This study highlights the necessity of an academic and objective approach to understanding the complexity of contemporary Islamic religious discourse.